Getting to No: Pragmatic and Semantic Factors in Two‐ and Three‐Year‐Olds' Understanding of Negation. Issue 4 (15th June 2017) - Reuter, Tracy; Feiman, Roman; Snedeker, Jesse
Abstract : Although infants say "no" early, older children have difficulty understanding its truth‐functional meaning. Two experiments investigate whether this difficulty stems from the infelicity of negative sentences out of the blue. In Experiment 1, given supportive discourse, 3‐year‐olds ( N = 16) understood both affirmative and negative sentences. However, with sentence types randomized, 2‐year‐olds ( N = 28) still failed. In Experiment 2, affirmative and negative sentences were blocked. Two‐year‐olds ( N = 28) now succeeded, but only when affirmatives were presented first. Thus, although discourse felicity seems the primary bottleneck for 3‐year‐olds' understanding of negation, 2‐year‐olds struggle with its semantic processing. Contrary to accounts where negatives are understood via affirmatives, both sentence types were processed equally quickly, suggesting previously reported asymmetries are due to pragmatic accommodation, not semantic processing.